Adverse Events and Technical Complaints of Technologies for the Management of Elimination Ostomies in Brazil (Estima – Brazilian Journal of Enterostomal Therapy, 2024)
Objective: To describe adverse events and technical complaints involving technologies for the management of elimination ostomies reported in Brazil. Method: This cross‑sectional descriptive study used secondary data recorded in the Notivisa system. The data encompass adverse events and technical complaints reported from January 2007 to August 2023. Descriptive statistical tools were used for the analysis. Results: A total of 2,812 notifications were identified, of which 101 (3.6%) were adverse events, and 2,711 (96.4%) were technical complaints. The state of São Paulo accounted for 884 (31.4%) notifications. Collection bags were the most frequently reported products, with 2,688 (95.6%) notifications, including 84 (3.1%) adverse events and 2,604 (96.9%) technical complaints. Regarding outcomes, 2,718 (96.7%) notifications lacked information, 19 (0.67%) reported urinary retention, 13 (0.46%) reported dermatitis, and 9 (0.32%) reported skin injury. Conclusion: The number of notifications has continued to rise in recent years; however, the quality remains low, as evidenced by the high rate of omitted information. Technical complaints about collection bags represent the largest number of notifications in Brazil. The description of outcomes in the use of products for ostomy management is unclear and may lead to the underreporting of significant adverse events such as dermatitis.